Changes in the structure of mortality due to COVID-19 in Czechia, Poland, and Slovakia - Dębicka, Joanna; Mazurek, Edyta; Špirková, Jana (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Objectives: The objective of our paper was to determine the statistical significance of the impact of the COVID-19 disease on the average age of death of an individual and the dependence of the average age of death on the causes of death in 2020. Study design: Awareness of the effects and consequences of the pandemic prompted us to check whether COVID-19 had a statistically significant impact on death patterns in Czechia, Poland, and Slovakia. Methods: The research is based on a detailed comparative analysis of the age structure of deaths from COVID-19 in countries that are regionally and culturally close. The Renkonen similarity index is calculated, followed by the non-parametric test for similarity of structures. Results: The average life expectancy in the analyzed countries decreased by about 1–2 years, and the forecasts of the increase in the number of deaths in 2020 turned out to be underestimated by 11% in the case of Slovakia and by 15% in the case of Poland and Czechia. COVID-19 was the fourth leading cause of death for women and the third leading cause of death for men in Poland and Czechia. In Slovakia, it was the third leading cause of death among women and the fourth among men.Conclusions: The pandemic caused not only direct deaths from the virus, but also indirect deaths due to the disruption of healthcare systems, socioeconomic shocks, and mental health consequences.
Keywords: index similarity of structure; life expectancy; age of death; COVID-19